Meet me at emotional baggage claim [compact disc, unabridged] - Scottoline, Lisa (Macmillan Audio, 2012)
Now that Lisa is a suburban empty-nester and Francesca is an independent twenty-something in the big city, they have to learn how to stay close while living apart. How does a mother's love translate across state lines and over any semblance of personal boundaries? You'll laugh out loud as they face-off over the proper technique for packing dishes, the importance of bringing a coat in the summertime, and the dos and dont's of dating at any age.